The Role of Notary in Making the Deed of Power of Attorney Imposing Mortgage on Land Collateral - Siti Rokhmah; Ahmad Khisni; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this study was to identify and analyze the role of the Notary in making the Deed of Power of Attorney for Imposing Mortgage Rights (SKMHT) on uncertified land collateral at Bank BPR Karya Remaja Indramayu Regency, along with obstacles and solutions. This study uses an empirical juridical approach and the specifications of this study use a descriptive analytical method with a qualitative approach. The sources and types of data in this study are primary data obtained from field studies with interviews. And secondary data obtained from literature studies related to the theory of legal certainty and authority. Based on the results of the study, it was concluded that in practice the Notary made SKMHT in accordance with Article 15 UUHT to bind collateral for uncertified land to be used as collateral, and had fulfilled what was stipulated in Article 38 of the UUJN regarding the beginning of the Deed, the body of the Deed, and the closing. Deed. The obstacles faced by Notaries are a). The inhibiting factor from the Bank, namely the incomplete document, b). The Inhibiting Factor from the Debtor is the problem of the amount of fees. c). Bad credit. The solutions to overcome these obstacles are: a). Give 7 working days to complete documents from the Bank or customer. b). Negotiated costs with a Notary, c). Banks are careful in providing credit.